Governing Global Higher Education and Science: IONAs and Ever-Renewing Webs of Interconnection - Gibson, Andrew (Routledge, 2024)
To speak of the interconnectedness of our world has become a truism since the most recent pulse of “globalisation”. Response to the pandemic has highlighted both the interconnectedness of the world and the interconnectedness of science. Indeed, in different ways, these events have challenged the nation state’s ability to withstand or respond effectively to the global. This tension has been evident in recent years, thus lending urgency to international forms of governance. As higher education and science are central to the challenges that face us as a planet, it is important to see in what ways international and global higher education and science are “governed”. Since the late eighteenth century, elites have sought to find ways to govern international connections, and in the twentieth century, this led to an alphabet soup of organisations. Research and science have been part of this process, as higher education began to transform itself from being a local institution embedded in its community to one which has been understood by states as useful for global positioning. This chapter illustrates that the proliferation of international organisations, networks, and associations (IONAs) central to governing global higher education, research, and development (HERD) has no signs of slowing and that the constant renewal of such connections is central to what makes a dynamic process of international cooperation. It also shows that the existence of webs of international, cross-border organisations of higher education constituting global governance is itself radically overdetermined. However, the process of integration and occasionally even coordination is not as comprehensive or complete as this picture might lead us to believe—and is often portrayed. And furthermore, it is by no means a one-way, one-time vectored system. The chapter has five sections: the first provides an overview of the changing higher education and research landscape and emergent issues; the second sets out a picture of governance in international HERD as coordination; the third discusses different perspectives on global governance of higher education and science; the fourth maps the webs of IONAs and associated tools; and finally, the fifth explains these developments in terms of what they tell us about the contemporary ecosystem of governing higher education.
The Routledge Handbook of Global and Digital Governance Crossroads
PUBLISHED
Keywords: International Integration; EDUCATION; Higher Education; Education; Policy